Rapid Detection of the Varicella-Zoster Virus Using a Recombinase-Aided Amplification-Lateral Flow System - Kathrina Mae Bienes; Lingjing Mao; Benjamin Selekon; Ella Gonofio; Emmanuel Nakoune; Gary Wong; Nicolas Berthet (Diagnostics, 2022)
Varicella-zoster virus (VZV) is the etiological agent of varicella (chickenpox) and herpes zoster (shingles). VZV infections are ubiquitous and highly contagious, and diagnosis is mostly based on the assessment of signs and symptoms. However, monkeypox, an emerging infectious disease caused by the monkeypox virus (MPXV), has clinical manifestations that are similar to those of VZV infections. With the recent monkeypox outbreak in non-endemic regions, VZV infections are likely to be misdiagnosed in the absence of laboratory testing. Considering the lack of accessible diagnostic tests that discriminate VZV from MPXV or other poxviruses, a handy and affordable detection system for VZV is crucial for rapid differential diagnosis. Here, we developed a new detection method for VZV using recombinase-aided amplification technology, combined with the lateral flow system (RAA-LF). Given the prevalence of VZV worldwide, this method can be applied not only to distinguish VZV from other viruses causing rash, but also to foster early detection, contributing substantially to disease control.